2020
DOI: 10.1155/2020/2825108
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Age-Related Changes in the Core Vestibular Projection Pathway and Balance Ability: A Diffusion Tensor Imaging Study

Abstract: Objective. We investigated the changes of the vestibulospinal tract (VST) and parietoinsular vestibular cortex (PIVC) using diffusion tensor imaging (DTI) and relation to balance between old and young healthy adults. Methods. This study recruited eleven old adults (6 males, 5 females; mean age 63.36±4.25 years) and 12 young adults (7 males, 5 females; mean age 28.42±4.40 years). The lateral and medial VST and PIVC were reconstructed using DTI. Fractional anisotropy (FA), mean diffusivity (MD), and tract volume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…Tandem gait is considered a useful marker of dysfunction in neurologic conditions 19 21 . Since the early nineteenth century, tandem gait testing has been used for the neurological examination of lower extremity dysfunction in patients with cerebellar disease, parkinsonism, vestibulopathies, and other conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Tandem gait is considered a useful marker of dysfunction in neurologic conditions 19 21 . Since the early nineteenth century, tandem gait testing has been used for the neurological examination of lower extremity dysfunction in patients with cerebellar disease, parkinsonism, vestibulopathies, and other conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Because both the VN and the PIVC are associated with dizziness, the above studies suggested that the CVP injury was associated with dizziness and coincided with the present results. Meanwhile, Yeo et al (2020) reported that the TV of the CVP was associated with age [48]. Thus, we recruited the patients who were younger than 50 years old in this study.…”
Section: Discussionmentioning
confidence: 99%
“…In DTI studies, Yeo et al ( 34 ) demonstrated patients with injury of the vestibulospinal tract following lateral medullary syndrome (e.g., loss of consciousness, ataxia, postural instability, confusion, headache, incoordination, and visual deficits) ( 4 ). In 2019, Yeo et al showed the relationship between the vestibular neural pathway, including the projection pathway to the PIVC and the vestibulospinal tract and balance according to aging.…”
Section: Discussionmentioning
confidence: 99%
“…In 2019, Yeo et al showed the relationship between the vestibular neural pathway, including the projection pathway to the PIVC and the vestibulospinal tract and balance according to aging. Moreover, DTI parameters in the vestibular neural pathway are associated with age-related reductions in balance ability ( 34 ). Together, these results commonly show that the PIVC is associated with central vestibular disorders and impairment of body movement, especially balance and gait function because PIVC encodes the vestibular signals contributing to self-motion perception ( 33 ).…”
Section: Discussionmentioning
confidence: 99%